2010
DOI: 10.1371/journal.ppat.1000769
|View full text |Cite
|
Sign up to set email alerts
|

The Syk Kinase SmTK4 of Schistosoma mansoni Is Involved in the Regulation of Spermatogenesis and Oogenesis

Abstract: The signal transduction protein SmTK4 from Schistosoma mansoni belongs to the family of Syk kinases. In vertebrates, Syk kinases are known to play specialized roles in signaling pathways in cells of the hematopoietic system. Although Syk kinases were identified in some invertebrates, their role in this group of animals has not yet been elucidated. Since SmTK4 is the first Syk kinase from a parasitic helminth, shown to be predominantly expressed in the testes and ovary of adult worms, we investigated its functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 84 publications
11
120
0
Order By: Relevance
“…The RNAi approach was already used in several areas of S. mansoni biology (Boyle et al 2003, Skelly et al 2003, Correnti et al 2005, Delcroix et al 2006, Dinguirard and Yoshino 2006, Freitas et al 2007, Krautz-Peterson and Skelly 2008b, Morales et al 2008, Pereira et al 2008, Faghiri and Skelly 2009, Rinaldi et al 2009, Beckmann et al 2010 as well as in S. japonicum (Cheng et al 2005, Zhao et al 2008, Kumagai et al 2009. RNAi has proved itself as an important tool to elucidate gene function in schistosomes, in a similar way as in other organisms.…”
Section: Short Non-coding Rnasmentioning
confidence: 99%
“…The RNAi approach was already used in several areas of S. mansoni biology (Boyle et al 2003, Skelly et al 2003, Correnti et al 2005, Delcroix et al 2006, Dinguirard and Yoshino 2006, Freitas et al 2007, Krautz-Peterson and Skelly 2008b, Morales et al 2008, Pereira et al 2008, Faghiri and Skelly 2009, Rinaldi et al 2009, Beckmann et al 2010 as well as in S. japonicum (Cheng et al 2005, Zhao et al 2008, Kumagai et al 2009. RNAi has proved itself as an important tool to elucidate gene function in schistosomes, in a similar way as in other organisms.…”
Section: Short Non-coding Rnasmentioning
confidence: 99%
“…To further develop transgenesis in schistosomes, it has been necessary to explore methods for stable germline transformation which would allow genetic as well as phenotypic studies in subsequent generations. Towards this end, we developed a modified particle bombardment protocol that allowed the introduction of transgenes into the germline using miracidia as targets (Beckmann et al 2007). After bombardment, the miracidia were still biologically active and able to infect snails to continue the life cycle -a critical step for the establishment and monitoring of stable transgenesis.…”
Section: T R a N S I E N T L Y T R A N S F O R M E D S C H I S T O S mentioning
confidence: 99%
“…These data demonstrated that transgenes can be passed on from one life stage to the next within one generation and, furthermore, from one generation to the next. Since the germ cells are considered to be the only constant cell line during schistosome development we could indirectly demonstrate the presence of transgenes in the germline and a successful germline-transformation approach (Beckmann et al 2007). However, the presence of the transgenes could not be detected from generation F 2 on.…”
Section: T R a N S I E N T L Y T R A N S F O R M E D S C H I S T O S mentioning
confidence: 99%
“…Isolation of genomic DNA and total RNA was performed as described elsewhere (Grevelding 1995, Beckmann et al 2010b). In short, DNA was isolated by a proteinase K-based procedure, followed by phenol/chloroform extraction and ethanol precipitation before resuspension in dH 2 O.…”
Section: Isolation Of Nucleic Acidsmentioning
confidence: 99%
“…For first experiments to interfere with cGK activity in schistosomes, the cGMP analog (PR)-8-pCPT-cGM-PS (Rp-8-(4-chlorophenylthio)-guanosine-39,59-cyclic monophosphorothioate) (Biolog, Germany) was used for in vitro studies with adult schistosomes following a previously described procedure (Beckmann et al 2010b). According to studies on purified cGKs, indicating a K i of 0,5μM or IC 50 of 18,3μM for cGKI and IC 50 of 0,16μM for cGKII (Butt et al 1994, Gamm et al 1995) the inhibitor was used in a 100fold higher concentration of 1 mM.…”
Section: Inhibitor Studies and Morphological Analysesmentioning
confidence: 99%